2021
DOI: 10.1177/15330338211033044
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Long Non-Coding RNAs and Various Types of Death in Cancer Cells

Abstract: With the increasing aging population, cancer has become one of the leading causes of death worldwide, and the number of cancer cases and deaths is only anticipated to grow further. Long non-coding RNAs (lncRNAs), which are closely associated with the expression level of downstream genes and various types of bioactivity, are regarded as one of the key regulators of cancer cell proliferation and death. Cell death, including apoptosis, necrosis, autophagy, pyroptosis, and ferroptosis, plays a vital role in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Since an increasing number of studies have indicated that non-coding RNAs may modulate the process of ferroptotic cell death ( 43 45 ). Herein, we also assessed the potential correlation of obtained ferroptosis gene signature with the lncRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Since an increasing number of studies have indicated that non-coding RNAs may modulate the process of ferroptotic cell death ( 43 45 ). Herein, we also assessed the potential correlation of obtained ferroptosis gene signature with the lncRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that hippocampal calmodulin-like 1 (HPCAL1) is an autophagy receptor that affects membrane tension by regulating CDH2, which further affects lipid peroxidation and ultimately inhibits ferroptosis in vitro and in vivo [ 88 ]. Another autophagy receptor, Tax1 (human T cell leukemia virus type I) binding protein 1 (TAX1BP1), promotes GPX4 degradation and subsequent ferroptosis in response to copper stress [ 89 ]. The above studies suggest a close association between autophagy and ferroptosis.…”
Section: Relationship Between Ferroptosis and Other Pcdsmentioning
confidence: 99%
“…The role of ncRNAs in tumorigenesis and immune response has been investigated widely in cancers. In these settings, ncRNAs regulate proliferation, differentiation, apoptosis, necrosis, autophagy, immune response, and inflammation [35,69,83,84]. In colorectal cancer, it was reported that the tumor suppressor miR-195-5p promotes TAM polarization by suppressing NOTCH2 expression [85].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%